The ha-ha eaudiobook - King, Dave (Recorded Books Inc., 2016)
Pushcart Prize nominee Dave King delivers a moving novel that explores the nature of family. Wounded in Vietnam, Howard Kapostash is unable to speak, read or write, although his intelligence is normal. Now middle-aged, he lives a lonely existence. But then his former high school sweetheart entrusts her nine-year-old son to Howard when she enters drug rehab. Suddenly a father figure, Howard begins to open up, and the emotional wounds of his past start to heal. ". lovingly rendered in careful, steady prose . explores familial bonds arising between people with no blood ties . with poise and heart."-Publishers Weekly